Anti-oxidative Effects and Toxicity of Bauhinia penicilliloba Ethanolic Leaf Extracts - Suparat Chanluang (Science Faculty of Chiang Mai University, 2019)
This study aimed to investigate the anti-oxidative effect and toxicity of Bauhinia penicilliloba ethanolic leaf extracts (EEBP). The EEBP was 23.45% from dried weight which yielded active purified fraction (AFBP) at 1.84%. The AFBP was phytochemical screened and found to be flavonoid which identified as rutin, quercetin and kaempferol by using HPLC. The scavenging activity of EEBP and AFBP was examined by DPPH (IC50=12.91±0.11 and 5.55±0.23 mg/mL) and ABTS assays (TEAC=0.60±0.02 and 4.93±0.15 mM). The reducing power of EEBP and AFBP which were conducted by FRAP assay, was 0.61±0.09 and 8.68±0.15 mM/mg. The EEBP and AFBP also inhibited TBARS formation in brain tissue (IC50=13.58±3.25 and 6.07±0.74 mg/mL). The phenolic contents of EEBP and AFBP were 77.71±1.43 and 4,162.59±81.90 mg/mg of gallic acid equivalents. LD50 values for acute toxicity of a single intra-gastric (i.g.) route administered to adult male and female mice were >6.00 g/kg BW, whereas, LD50 values of intra-peritoneal (i.p.) route were >4.00 g/kg BW and 2.77 g/kg BW. Sub-chronic toxicity was conducted by given orally of the EEBP for 8 weeks. The body weight, organ weight, AST, ALT, ALP, Cr and BUN serum levels were not altered. Our study suggests that B. penicilliloba may have a considerable potential for further development as a new anti-oxidative agent.